Reliability analysis of power electronics for heavy hybrid vehicle applications - Martin, Strängberg (My University, 2014)
The purpose of the thesis report is analyze the reliability of power electronics for heavy hybrid vehicles. The failure modes of the power electronics are investigated, along with lifetime analysis with respect to different current levels and compared with the lifetime information provided by the manufacturer. In the power electronics module both the IGBTs and the diodes are tested. The report focuses on active power cycling. Passive cycling is when the test object is thermally cycled from the surrounding temperature and active power cycling is when the test object is heated up by a current, during cool down the current is stopped. The time for heating up is 2 s and the cooling down time is 2 s, generally for short time cycles the bond wire is the major cause of failure, for longer time periods solder delamination becomes a problem. The tests are done with an on time of 2 seconds, with this time cycle the bond wires are the part most likely to be the cause of failure. The lifetime of the modules varied between 56 000 and 380 000 cycles depending on the temperature swing, ΔT, and if it is a diode or an IGBT. For the highest temperature swing, of both the diode and the IGBT, the result is as expected when compared to the manufacturers lifetime curve. For the other temperature swings the lifetime is longer than expected. Since it seems that the failure were caused by the bond wires, longer time periods are needed if the test should be done to find when the modules fails because of solder delamination. Also passive cycling should be investigated together with other types of tests such as vibration and chemical tests to investigate if the modules are suitable for operation in a heavy hybrid vehicle.
Keywords: Energi; Elkraftteknik; Energy; Electric power engineering